(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Fire safety is a critical issue in industrial settings, where the risk of fire can lead to significant damage, loss of life, and environmental impact. This article explores the common fire safety problems in industrial enterprises, analyzes existing literature on fire prevention and response, and presents methods to mitigate risks. By examining case studies and statistics, the study highlights potential solutions and provides recommendations for enhancing fire safety protocols.